Crude palm oil market volatility: Malaysian evidence - Haron, Razali; Salami, Monsurat Ayojimi (2014)
This study aims to examine the volatility of Malaysian Crude Palm Oil (CPO) market since it is apparent that market volatility has important implication to both investors and policy makers.This study adopted GARCH(1,1) model in examining the market volatility of Malaysian CPO commodity market. The result of the finding indicated that Malaysian CPO market exhibits persistent volatility as well as volatility clustering. The persistent volatility indicates that the percentage of market volatility is closer to unity while the volatility clustering provides useful information on every event of a shock. A more informed decision may be made with adequate understanding of the degree of volatility in the Malaysian CPO market. Hence,the essence of hedging in Malaysian CPO futures market is deduced through the result of the findings. This study is different from previous studies on Malaysian CPO market as the volatility of the market is examined in detail and the half-life decay of the market volatility is also quantified.